2022
DOI: 10.3390/polym14071480
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Multilayer Composite Hollow Membrane in Separation of CO2 from CH4 in Mixed Gas Conditions

Abstract: Composite membranes comprising NH2-MIL-125(Ti)/PEBAX coated on PDMS/PSf were prepared in this work, and their gas separation performance for high CO2 feed gas was investigated under various operating circumstances, such as pressure and CO2 concentration, in mixed gas conditions. The functional groups and morphology of the prepared membranes were characterized by Fourier transform infrared spectroscopy (FTIR) and field emission scanning electron microscopy (FESEM). CO2 concentration and feed gas pressure were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…One of the promising strategies for improving the separation performance of membranes in the separation of CO 2 is a composite structure of organic-inorganic multilayer hybrid membranes [5,6]. The motivation for fabricating multilayer hybrid membranes is to achieve a high performance membrane at low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the promising strategies for improving the separation performance of membranes in the separation of CO 2 is a composite structure of organic-inorganic multilayer hybrid membranes [5,6]. The motivation for fabricating multilayer hybrid membranes is to achieve a high performance membrane at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some expensive and high performance materials can be used [7]. Several review papers have reported that PEBA (Polyether block amide) polymer as an organic membrane has excellent potential for separating acid gas such as CO 2 , and can be used as a selective top layer in multilayer hybrid membranes [6,[8][9][10]. The multilayer hybrid membrane with high selective top layer must have a suitable sublayer.…”
Section: Introductionmentioning
confidence: 99%